CHANGES IN DUAL-TASK GAIT VELOCITY COST FOLLOWING CONCUSSION. Issue 7 (30th July 2021) - Ernest, Kristin M.; Davis, Tyler; Dugan, Eric L
Background: Changes in gait velocity have been identified in the literature between concussed and non-concussed individuals. Concussed patients demonstrate slower gait speed; the gait velocity cost has not been evaluated as extensively. Hypothesis: Hypothesis 1: Dual-task gait velocity cost will decrease at time of clearance compared to initial testing. Hypothesis 2: Subjects with a SRC will demonstrate greater decreases in gait velocity costs than those with non-SRC. Hypothesis 3: Symptom severity will be positively correlated to dual-task gait costs within the first 5 days after concussion. Methods: Patients evaluated for concussion in primary care sports medicine clinic within five days of injury were recruited between October 2017 and May 2019. The mechanism of injury was documented and used to classify sport-related (SRC) versus non sport-related (non-SRC) concussion. A standard concussion evaluation was performed at each visit to assess history, symptoms, neurocognitive, neuromuscular and vestibular dysfunction. Dual-task walking trials were incorporated with a cognitive task such as reciting the months of the year in reverse order or spelling words backwards. During the walking trials, gait velocity was measured using an Xsens MVN BIOMCH system (Xsens Technologies BV, Enschede, The Netherlands). A two-way mixed ANOVA with one within-subjects factor (time) and one between-groups factor (mechanism of injury) was used to determine if dual-task gait velocity costs differed over time and between those with a SRC versus those with a non-SRC. A Pearson's product-moment correlation was used to assess the relationship between symptom severity scores and dual-task gait costs at initial visit. Results: There was no statistically significant interaction between the mechanism of injury and time on gait velocity cost, F (1, 79) = .033, p = .86. The main effect of time showed a statistically significant difference in mean gait velocity cost from initial to clearance, F (1, 79) = 6.19, p = 0.015, generalized η 2 = .0.013. There was no main effect of mechanism of injury in mean gait velocity costs, F (1, 79) = 0.800, p = 0.374, generalized η 2 = 0.008. There was a statistically significant, small positive correlation between symptom severity and dual-task gait velocity costs, r = .30, p < .007, with symptom severity explaining 9 % of the variation in dual-task gait velocity costs. Conclusion: The gait velocity cost demonstrates a statistically significant change from the time of injury to clearance in concussion patients. A small but significant relationship also exists between symptom severity and gait velocity cost.